Tổng hợp perovskit LaFeO3 cấu trúc nano bằng phương pháp đốt cháy gel - Đại, Lưu Minh; Nhiệm, Đào Ngọc; Ninh, Vũ Thế; Chức, Phạm Ngọc; Lịm, Dương Thị (Vietnam Journal of Chemistry, 2014)
The nanostructured powder of LaFeO3 has been synthesised at low temperature (550 oC) via the combustion of gel prepared by polyvinyl alcohol (PVA) and corresponding metal nitrates. Samples were characterized by diffraction (XRD), scanning electron microscopy (SEM). Further thermal treatment at 550 oC for 2 hours yields the single phase LaFeO3 with average size < 50 nm. Keywords: LaFeO3, hydrothermal method, polyvinyl alcohol (PVA), combustion method.